Loss-of-function mutations in ADCY3 cause monogenic severe obesity. (February 2018) - Saeed, Sadia; Bonnefond, Amélie; Tamanini, Filippo; Mirza, Muhammad; Manzoor, Jaida; Janjua, Qasim; Din, Sadia; Gaitan, Julien; Milochau, Alexandra; Durand, Emmanuelle; Vaillant, Emmanuel; Haseeb, Attiya; et al.
Abstract Study of monogenic forms of obesity has demonstrated the pivotal role of the central leptin–melanocortin pathway in controlling energy balance, appetite and body weight1 . The majority of loss-of-function mutations (mostly recessive or co-dominant) have been identified in genes that are directly involved in leptin–melanocortin signaling. These genes, however, only explain obesity in <5% of cases, predominantly from outbred populations2 . We previously showed that, in a consanguineous population in Pakistan, recessive mutations in known obesity-related genes explain 30% of cases with severe obesity3–5 . These data suggested that new monogenic forms of obesity could also be identified in this population. Here we identify and functionally characterize homozygous mutations in theADCY3 gene encoding adenylate cyclase 3 in children with severe obesity from consanguineous Pakistani families, as well as compound heterozygous mutations in a severely obese child of European-American descent. These findings highlight ADCY3 as an important mediator of energy homeostasis and an attractive pharmacological target in the treatment of obesity. Genetic analysis of children with severe obesity identifies mutations in theADCY3 gene (encoding adenylate cyclase 3). These variants are rare in public databases and affect the functional activity of the protein, indicating that ADCY3 is a potential pharmacological target for obesity treatment.